Free radical processes in the mitochondrial fractions of rats’ liver under the conditions of bisphenol A administration and low-level laser irradiation - Borschovetska, Vira (Збірник тез конференції-конкурсу молодих вчених «Актуальні проблеми біохімії та біотехнології – 2021», 2021)
The aim of this study is to investigate the effect of low-level laser irradiation on oxidative stress parameters in mitochondrial fractions of rats under the conditions of BPA administration.
The abstract of report
Keywords: free radicals, bisphenol A, LLLI